Silibinin Inhibits NSCLC Metastasis by Targeting the EGFR/LOX Pathway - Hou, Xiaoying; Du, Hongzhi; Quan, Xingping; Shi, Lei; Zhang, Qianqian; Wu, Yao; Liu, Yang; Xiao, Jing; Li, Yong; Lu, Ligong; Ai, Xun; Zhan, Meixiao; et al. (Frontiers in Pharmacology, 2018)
Tumor metastasis is the most lethal and debilitating process that threatens cancer patients. Among the regulators involved in tumor metastasis, lysyl oxidase (LOX) is an important contributor for tumor invasion, migration and the formation of the pre-metastatic niche. Although the relationship between LOX and poor prognosis of lung patients has been preliminary reported, the mechanism remains poorly understood. Here, we found that LOX overexpression is closely related to the survival of lung adenocarcinoma patients but not squamous cell carcinoma patients. Moreover, we confirmed that LOX expression is regulated by the activation of epidermal growth factor receptor (EGFR) via the PI3K/AKT, MEK/ERK and SAPK/JNK signaling pathways in NSCLC. Meanwhile, the study also suggested that the traditional anti-fibrosis drug silibinin inhibited NSCLC cell migration in an EGFR/LOX dependent manner. In addition, an orthotopic implantation metastasis model also confirmed that the EGFR inhibitor WZ4002 and silibinin decreased tumor metastasis through the EGFR/LOX pathway. Altogether, this study revealed that LOX expression is regulated by the EGFR pathway and this may account for the anti-cancer metastasis effects of silibinin, indicating LOX as a potentially therapeutic target for NSCLC treatment.